Biodiversity conservation and sustainable use: Malaysian scenario - Sofian-Azirun, Mohd; Rashid, Y.N. (2009)
Malaysia is in partnership to international agreements such as for Biodiversity, Climate Change, Endangered species, Hazardous wastes, Marine life conservation, Tropical timber 83 and Law of the sea. Like all countries in the pact, she is currently implementing the national biodiversity strategies and action plans that have been strategized. The progression has led to increase in awareness of biodiversity status and enhancement of protected areas, with current statistics of 63% acclaimed forests and woodland in contrast to 10% land use for permanent crops. In spite of this there are indicative trends that Malaysia too contributes to the 42% loss of the Southeast Asian biodiversity approaching 2100. Here we highlight the challenged in conservation efforts and three primary driving forces impacting upon biodiversity: • Conversion of natural habitat to human ecosystem • Natural disasters and climate change • Bioprospecting Malaysia's strategic location within Southeast Asia, with Thailand in the north, Singapore in the south and Brunei in the east would need a multidisciplinary approach in order to address issues of biodiversity threats which one country has on its neighbours. This will be discussed in three main components: • Invading operational activities • Domestic activities • Resources affected by international activities In summary, a realistic solution would be an overall participation from all major stakeholders and a trasboundary effort such as the international ecological footprint.